Arc stud welding of dissimilar AISI 420 to AISI 316L stainless steels - Muhaed Alali; Athil S. Al-Ezzi; S. M. Anas; Farman Salim; Sami A. Nawi; M. H. Abass; Abeer A. Shehab; Ali A. Al Katawy; Ahmed A. A. G. Alrubaiy (Discover Materials)
Abstract This study investigates the joining of AISI 316L austenitic stainless steel (ASS) and AISI 420 martensitic stainless steel (MSS) using arc stud welding. The arc stud process is essential to the aerospace, automotive, and marine engineering industries, where robust and dependable dissimilar metal joints are crucial. This study investigates arc stud welding as a quick and effective substitute for TIG, MIG, and laser welding, which are the main focus of earlier research. Metallographic analysis revealed significant microstructural variations across the base metal (BM), heat-affected zone (HAZ), and fusion zone (FZ). The 'FZ' exhibited an austenitic microstructure with fine dendritic formations due to rapid cooling, while an applied Post Welding Heat Treatment (PWHT) transformed the HAZ into coarser tempered martensite, enhancing mechanical properties and reducing brittleness. Welding at 600 A for 0.2 s achieved the highest tensile strength represented by breaking force, but extending the duration to 0.3 s at the same current reduced the tensile strength due to excessive heat-induced brittleness. Conversely, at 400 A, tensile load peaked at 0.3 s, preserving finer grain structures. Hardness measurements in AISI 420 varied from 190 to 633 HV, indicating potential cracking risks. After PWHT, hardness improved to 188–348 HV, demonstrating a reduction in residual stresses, improved ductility, and enhanced toughness in the 'HAZ' and 'FZ'. These findings highlight the novel application of arc stud welding for dissimilar stainless-steel joints and emphasize the importance of optimizing welding parameters and PWHT to enhance mechanical performance and structural integrity.